'Our surgeons want this to be short and simple': practices of in-hospital medication review as coordinated sociomaterial actions. Issue 3 (2nd September 2018) - Reichenpfader, Ursula; Wickström, Anette; Abrandt Dahlgren, Madeleine; Nilsen, Per; Carlfjord, Siw
ABSTRACT: Medication review, a systematic assessment of a patient's medicines by a health care professional, is intended to prevent medication-related harms. A critical element of medication review concerns whether medication review is conducted in a coordinated way. This article draws from a case example of implementing medication review in two surgical wards of a Swedish regional hospital and aims to analyse how medication review is being accomplished with respect to the coordination of its actions. Using a practice-based ethnographic approach, we present several coordination mechanisms by illustrating how practices are connected to materials involved in medication review. Also, we show how common orientations, ends, and understandings expressed in different medication review practices contribute to the coordination of the practices. In conclusion, this article highlights the complexity of establishing and sustaining medication review as a coordinated practice in routine health care. By closely examining sociomaterial connections, this article sheds new light on the neglected issue of artefacts and arrangements in constituting and transforming a highly complex medication practice.